Kate Carnegie and Those Ministers - Maclaren, Ian, 1850-1907 (Salt Lake City, UT : Project Gutenberg, 2007)
"Kate Carnegie and Those Ministers" by Ian Maclaren is a novel written in the late 19th century. The story centers around the life of Kate Carnegie, a spirited young woman, and her interactions with various characters in her Scottish community, particularly a young minister named Carmichael. The book captures the warmth of small-town life along with explorations of community dynamics, tradition, and personal growth. At the start of the novel, readers are introduced to the lively chaos of Muirtown Station as it prepares for the arrival of travelers and their baggage. Amidst this bustle, we meet John Carmichael, a young and passionate minister who is described as being not only personable but also deeply empathetic toward animals and people alike. The narrative juxtaposes Carmichael's character against the backdrop of his return to the parish of Drumtochty, where he is on the cusp of a significant encounter with Kate Carnegie. Their first meeting at the station is marked by comic miscommunication and mutual curiosity, setting the stage for a relationship characterized by both humor and depth, intertwined with themes of tradition and change in their time. (This is an automatically generated summary.)
Release date is 2007-01-19
E-text prepared by Al Haines
Keywords: Domestic fiction; Scotland -- Social life and customs -- 19th century -- Fiction; Country life -- Scotland -- Fiction